Key game-related statistical parameters predicting performance index rating for u16, u18, and u20 basketball players in different playing positions - Rajkovic, S.; Ðokic, Z.; Beretic, I.; Ahmetovic, Z. (Sports Science and Health, 2025)
The aim of this study was to determine which game-related statistical parameters could be used to predict the performance index rating of U16, U18, and U20 basketball players in different playing positions. A total of 167 games (box scores for 1813 players) of the finalists teams were analyzed at the FIBA Youth European Championships for men held from 2017-2022 across age categories: U16 (55 games, 595 players), U18 (56 games, 618 players) and U20 (56 games, 600 players). The game-related statistical parameters gathered as independent variables included: total points scored, free throw, 2 and 3-points attempts and made, rebounds, assists, steals, turnovers, personal fouls and blocks. The dependent variable was the Performance Index Rating. The basic descriptive statistics were calculated, while the models of depen- dency among the observed variables were defined using multiple regression analysis (backward method) at the significance level of p = 0.05. For players in outside positions, total points scored, assists, steals and offensive and defensive rebounds have a positive impact on their performance index rating. A number of 2-point and free throw attempts, turnovers, 3-point attempts, blocks against and personal fouls committed, have a negative impact. For players in inside positions, positive impact have a number of made 2 and 3-point shots, as well as assists, steals, defensive rebounds and blocks in favour. The negative impact included a 2-point shot attempts, turnovers, and personal fouls committed. These results can help coaches design more effective training programs, to prioritize offensive and defensive skills that positively impact a player`s per- formance.